A BODIPY decorated multiple mode reusable paper-based colorimetric and fluorometric pH sensor. (September 2022) - Öztürk, Dilek; Ömeroğlu, İpek and Köksoy, Baybars and Göl, Cem and Durmuş, Mahmut
Abstract: In this study, two difluoroboradiazaindacene (BODIPY) compounds bearing diethylaminostyryl groups were synthesized in order to establish colorimetric and fluorometric paper-based pH sensors. The structures of these novel BODIPY compounds were identified by NMR ( 1 H, 13 C, 11 B, and 19 F), elemental analysis, MALDI-TOF, FT-IR, UV–vis and fluorescence spectroscopies as well as single-crystal X-Ray data. The DFT study was also performed to optimize of these two novel BODIPY structures. Electrochemical measurements were applied to estimate their redox potentials. Photophysical properties such as fluorescence quantum yield and lifetimes were investigated to determine the effect of acid addition in both DMSO and 1, 4-dioxane solutions of the studied BODIPY derivatives. Also, pKa values of the synthesized compounds (1a and 1b ) were determined from absorbance and fluorescence measurements by acid titration studies. The paper-based pH sensor behavior of these BODIPY derivatives was investigated and their performances were determined on the lemon juice samples as a real sample analysis. A simple, cost-effective, rapid, portable, colorimetric, and fluorometric paper-based BODIPY sensing platform was developed in this study for the detection of the variety of pH changes in lemon juice. Graphical abstract: Image 1 Highlights: Novel mono and di-styryl BODIPY derivatives were designed and synthesized for the first time. Paper-based colorimetric and fluorometric pH sensors were obtained. The real sample analysis was performed using lemonjuice. The reusable, reversible, sensitive and cheap sensor platform was developed to pH changes.